1999
DOI: 10.1523/jneurosci.19-20-08830.1999
|View full text |Cite
|
Sign up to set email alerts
|

Domains Responsible for Constitutive and Ca2+-Dependent Interactions between Calmodulin and Small Conductance Ca2+-Activated Potassium Channels

Abstract: Small conductance Ca(2+)-activated potassium channels (SK channels) are coassembled complexes of pore-forming SK alpha subunits and calmodulin. We proposed a model for channel activation in which Ca2+ binding to calmodulin induces conformational rearrangements in calmodulin and the alpha subunits that result in channel gating. We now report fluorescence measurements that indicate conformational changes in the alpha subunit after calmodulin binding and Ca2+ binding to the alpha subunit-calmodulin complex. Two-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
222
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(244 citation statements)
references
References 43 publications
(37 reference statements)
19
222
3
Order By: Relevance
“…The binding of Ca 2ϩ to the EF hands results in the creation of a surface that serves as an interface for the association of CaM with the target protein. Each lobe can control distinct processes in the target protein (21,22), and binding to a target can change the affinity for Ca 2ϩ (23).…”
Section: Determinants In Cam That Are Required For Binding Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of Ca 2ϩ to the EF hands results in the creation of a surface that serves as an interface for the association of CaM with the target protein. Each lobe can control distinct processes in the target protein (21,22), and binding to a target can change the affinity for Ca 2ϩ (23).…”
Section: Determinants In Cam That Are Required For Binding Tomentioning
confidence: 99%
“…These Asp to Ala mutations in the EF hands greatly diminish or abolish their ability to bind Ca 2ϩ (21,24,25). Both mutants were able to interact with the C-terminal region of KCNQ2 or KCNQ3, although less strongly than wild type CaM.…”
Section: Determinants In Cam That Are Required For Binding Tomentioning
confidence: 99%
“…When expressed in Xenopus oocytes, the resulting channels are voltage-insensitive and activated by submicromolar intracellular Ca 2ϩ (Kohler et al, 1996;Hirschberg et al, 1998). Structurefunction analysis revealed that their Ca 2ϩ gating is mediated by constitutive association with calmodulin (Xia et al, 1998;Keen et al, 1999). However, direct interaction of calmodulin with native brain SK channels so far has been demonstrated only for SK3 (Xia et al, 1998).…”
mentioning
confidence: 99%
“…Therefore, we tested CaM 12 and CaM 34 mutant proteins, in which Ca 2+ binding to only the N-or C-lobe EF hands is altered, respectively. Because the CaM 12 mutation is known to suppress rSK2 current in a manner similar to CaM 1234 (Keen et al, 1999), we used an experimental design identical to that described in the preceding paragraph for CaM 1234 . Like CaM 1234 , CaM 12 effectively suppressed rSK2 current ( Fig.…”
Section: Mutant Cam Overexpression Does Not Affect Crac Channel Inactmentioning
confidence: 99%
“…The CaM 34 mutant does not affect rSK2 gating (Keen et al, 1999), but it is known to suppress CDI of the voltage-gated channel Ca V 1.2 (Peterson et al, 1999). Thus, as a positive control for knockdown of CaM function by CaM 34 , we compared inactivation of Ca V 1.2 currents carried by Ca 2+ and Ba 2+ (which supports only voltagedependent inactivation; see Materials and methods and Fig.…”
Section: Alignment Of Crystal Structures Predicts Steric Clash Of Cammentioning
confidence: 99%